MiR-21 promotes EGF-induced pancreatic cancer cell proliferation by targeting Spry2. Issue 12 (December 2018) - Zhao, Qiuyan; Chen, Sumin; Zhu, Zhonglin; Yu, Lanting; Ren, Yingchun; Jiang, Mingjie; Weng, Junyong; Li, Baiwen
Abstract Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant cancer that lacks effective targets for therapy. Alteration of epidermal growth factor (EGF) expression has been recognized as an essential molecular event in pancreatic carcinogenesis. Accumulating studies have demonstrated that miRNAs play critical roles in EGF signaling regulation, tumor initiation, cell proliferation and apoptosis. Here, we demonstrated that miR-21 expression was induced by EGF in pancreatic cancer cells. miR-21 promoted EGF-induced proliferation, inhibited cell apoptosis and accelerated cell cycle progression. In vivo experiments confirmed the influence of miR-21 on tumor growth. Mechanistic studies revealed that miR-21 targeted MAPK/ERK and PI3K/AKT signaling pathways to modulate cell proliferation. In addition, Spry2 was proven to be a target of miR-21. Furthermore, miR-21 and Spry2 were significantly related to clinical features and may be valuable predictors of PDAC patient prognosis.